Natural Resource Management Principles and the Role of Law in Realizing Good Development Governance - Nugraha, Satriya (PT. Riset Press International, 2024)
The impact is that development will result in environmental destruction or pollution of the environment; it can be understood that, in fact, development is a disturbance or problematic natural and environmental balance. The research aims to discover the principles of natural resource management and the role of law in realizing good development governance. This paper used research with normative-empirical legal methods by looking at what happens in cases or facts that exist in the principles of natural resource management and the role of law in realizing good development governance. In essence, development in its implementation must be balanced with using natural resources that can impact the environment. Natural resources can have an impact on the environment itself in the prevention of damage to reduce the level of environmental damage. Prevention of damage To reduce environmental damage, it is necessary to implement development that pays attention to protection and environmental management. There must be support and publicity for the environmental law system. The first is the need for ease of natural resource management (stakeholders) to be fair to the community, and the second is the need for ease of natural resource management (stakeholders). To be fair to the community, secondly, there is a need for legal relaxation through a structure to weaken criminalization by criminalization actions using an early filtering system and increase the independence of the law guardians' profession through the prioritization of the ultimum remedium principle, and then the third is to continue to see a law-aware society, especially stakeholders in the sustainable use of natural resources remain sovereign for food and energy independence and continue to grow.